INVOLMENT OF METALLIC NICKEL WASTE IN THE CHARGE FOR THE SMELTING OF HEAT-RESISTANT NICKEL ALLOYS - Нестеренко, Тетяна; Нестеренко, Ольга; Діденко, Лідія; Іванніков, Сергій (SWorldJournal, 2024)
An analysis of modern technologies and equipment for smelting heat-resistant nickel alloys, ways of processing waste from the production and consumption of nickel with their involvement in a closed cycle was carried out. The technology of refining electr